Screening of Aspergillus for citric acid production from Palm Oil Mill Effluent - Jamal, Parveen; Alam, Md. Zahangir; Mohd Salleh, Mohammad Ramlan; Nadzir, M. M. (Asian Network for Scientific Information, 2005)
In this study, screening of potential microbes, especially Aspergillus, for citric acid production from Palm Oil Mill Effluent (POME) is carried out to improve the product yield. The fermentation of the raw material POME for the production of citric acid was conducted by the liquid state fermentation process. A total of ten strains of Aspergillus were selected for the screening test of which six strains were isolated from Sewage Treatment Plant Sludge (STP Sludge), purified and identified up to genus level and four strains of Aspergillus were from lab stock. All strains were screened under controlled fermentation conditions such as pH range of 2-3, temperature 30°C and agitation 150 rpm, using 1% (w/w) of substrate (POME), 2% (w/w) co-substrate (wheat flour) with inoculum size of 2% (106 spore mL 1). These strains were examined in terms of maximum citric acid production, biosolid production (TSS%) and Chemical Oxygen Demand (COD) removal. The strain Aspergillus (A103) produced the highest concentration of citric acid (0.28 g L 1), TSS (12.7 g L 1) and COD removal (72%) followed by A1020, A-SS106 and others on 2-4 days of fermentation.